PENGARUH RASIO KEMANDIRIAN, EFEKTIFITAS DAN PERTUMBUHAN PADA KABUPATEN SOPPENG - Evamitria -; Hasmin Tamsah (Jurnal Mirai Management, 2016)
ABSTRACT This study attempts to 1) To know influence of independence ratio on financial performance of Soppeng Regency. 2) Influence the effectiveness of the performance of the local government finance on financial management agency and assets Area Soppeng Regency 2013-2015 years. 3) Influence the ratio growth of the performance of the local government finance on financial management agency and assets Area Soppeng Regency 2013-2015 years. 4) Influence the ratio independence, the ratio effectiveness and the growth of the performance of the local government finance on financial management agency and assets Area Soppeng Regency of the years 2013-2015. The result showed that 1) the independence of the Soppeng Regency has Positive significant against efficiency pad in the past three years (2013-2015). 2) the ratio of the effectiveness of the Soppeng Regency has positive significant against efficiency pad in the past three years (2013-2015). 3) a partial, the ratio of growth the Soppeng has regency negative and not significant against efficiency pad in the past three years (2013-2015). 4) the ratio of independence, effectiveness, and ratio growth significant against efficiency pad in the past three years (2013-2015). Keywords : Ratio of Independence, Effestiveness Ratio, Growth Ratio, Efficiency Ratio, Revenue (PAD)